Southern agency and digital education: an ethnography of open online learning in Dili, Timor-Leste. Issue 3 (3rd July 2019) - King, Monty; Forsey, Martin; Pegrum, Mark
ABSTRACT: This ethnography, based on fieldwork in Dili, Timor-Leste between 2015 and 2017, adopts an orthodox sociological theorising of agency to investigate the ways in which people in Dili negotiate the numerous interacting structural barriers to digital education. Having identified a lack of attention to learner agency in the literature on the promotion and adoption of MOOCs and OER in the Global South (King, Pegrum, and Forsey [2018]. 'MOOCs and OER in the Global South: Problems and Potential'. International Review of Research in Open and Distance Learning 19 (5): 2–20. doi:10.19173/irrodl.v19i5.3742 ), the paper addresses Connell's [(2008). Southern Theory: The Global Dynamics of Knowledge in Social Science . Crows Nest: Allen & Unwin] influential criticism of the imbalances in global knowledge production, and explores the parallels in technologically enhanced learning. A new concept- Southern agency- is developed through the stories of three Timorese students and their engagement with digital education, focussing on the influences of local infrastructure, family, literacies and the colonial legacy. The paper highlights the need for more extensive research into local practices of learning with technologies and advocates Southern agency as a heuristic device to gain valuable insights into the lived experience of Southern learners.